PERCEIVED LEGITIMACY OF INSIDER VS. OUTSIDER SUCCESSORS AND ITS IMPACT ON ORGANIZATIONAL PERFORMANCE IN THE ACCRA METROPOLIS - Mahama Alhassan Iddrisu Zaapayim, Abdul Jalil (International Journal of Engineering Technologies and Management Research, 2025)
Succession planning is a critical process for ensuring organizational continuity and performance, with the selection of insider or outsider successors playing a pivotal role. This study examines the perceived legitimacy of insider versus outsider successors and their impact on organizational performance within the Accra metropolis. Using the upper echelons theory as a framework, the study employed a quantitative research design with a sample size of 300 participants, comprising employees and stakeholders from organizations that had undergone leadership transitions within the last three years. Data were analyzed using descriptive and inferential statistical techniques, including correlation and regression analyses. The findings revealed a strong positive relationship between perceived legitimacy and organizational performance, with perceived legitimacy accounting for 90.9% of the variance in performance outcomes. Insider successors were viewed as fostering continuity and alignment with organizational culture, while outsider successors were associated with innovation and strategic change. These results highlight the importance of transparent and credible selection processes in leadership transitions. The study underscores the relevance of the upper echelons theory in understanding leadership dynamics and provides practical recommendations for improving organizational outcomes through effective succession planning.